Reexamination of a putative diploid hybrid Taxon using genetic evidence: The distinctiveness of Phlox pilosa subsp. deamii (Polemoniaceae) - Fehlberg, Shannon D.; Ty, Maureen M. C.; Ferguson, Carolyn J. (My University, 2014)
Premise of research. A number of recent studies have shown that hybridization plays a key role in the evolution of plants and can lead to the development of genetic and taxonomic novelty, even without a change in ploidy level. Documenting patterns of population genetic diversity for taxa of proposed homoploid hybrid origin and their putative parents leads to an improved understanding of the role of hybridization in the generation of plant diversity. Methodology. Phlox pilosa subsp. deamii is hypothesized to have arisen from diploid hybridization between P. pilosa subsp. pilosa and Phlox amoena. Here we analyzed 18 populations representing all three taxa using a population genetic approach, including microsatellite and chloroplast DNA sequence data. We addressed questions concerning genetic diversity and structure, hybrid origin, and ongoing evolutionary processes. Pivotal results. Several different analyses revealed that genetic variation in P. pilosa subsp. deamii was a mixture of (or was intermediate to) the genetic variation found in P. pilosa subsp. pilosa and P. amoena. However, populations of P. pilosa subsp. deamii were also notably distinct genetically and maintained high levels of genetic diversity. Comparisons between nuclear and chloroplast genetic data provided some evidence for ongoing gene exchange within this system. Conclusions. Phlox pilosa subsp. deamii is distinctive in its genetics, as well as its morphology and ecology. Combined with data from previous studies, population genetic data support a diploid hybrid origin for P. pilosa subsp. deamii, although with sufficient time since its origin for establishment of unique genetic variation. Furthermore, its formation may have come about through complex interactions among the closely related parental taxa, potentially with multiple hybrid generations, backcrossing, and introgression. Such a complex scenario of formation for this subspecific taxon raises questions with respect to the current distinction we make between homoploid hybrid origin of taxa, which is viewed as rare, and introgression, which is undoubtedly prevalent in plants.
Keywords: Genetic diversity; Hybrid origin; Hybrid species; Introgression; Microsatellites; Phlox; Reproductive isolation